INOVASI PEMANFAATAN TUMBUHAN SERAI WANGI (CYMBOPOGON NARDUS) MENJADI MINYAK ATSIRI GUNA MEWUJUDKAN EKONOMI KREATIF MASYARAKAT DESA SEDAU - Nurhidayanti, Nurhidayanti; Agustin, Rizki Dwi; Mujiburrahman, Mujiburrahman; Asmawati, Asmawati; Septiana, Dini; Yulianto, Dian Dwi; Insyiroh, Salsabila; Lana Safitri, Lana Safitri; Akbar, Djalaludin M.; Hanangga, Lalu Danal (Universitas Mataram, 2023)
Sedau Village is one of the villages in the Narmada sub-district, West Lombok district, West Nusa Tenggara province. Most of the people in Sedau Village are more interested in growing fruits, some other residents are planting medicinal plants. Citronella plants are cultivated by some residents of Sedau Village in small quantities, so they have not been able to provide economic benefits for the local community. In addition, there is also no community in Sedau Village who can process citronella plants into essential oil which can increase the selling price of the citronella. The purpose of this series of socialization and training activities by the Unram Thematic KKN team is to increase people's understanding and creativity about medicinal plant demonstration plots, how to cultivate several medicinal plants in the demonstration plot, especially citronella and post-harvest processing methods of citronella into essential oils , so as to increase the selling price of the fragrant citronella. The method used in this activity is the socialization method, participative through training and learning. While the technique used in distillation is the steam distillation process to obtain essential oils. Citronella oil is usually light yellow to dark yellow in color, and is volatile. Essential oil itself is an oil produced by plants. The resulting aroma is fragrant according to the producing plant, generally insoluble in water but soluble in organic solvents. The citronella oil distillation process consumes around 15-20 kilograms of raw materials with a distillation time of approximately 3 hours. From the distillation of citronella, 125 ml of essential oil was obtained.